Advanced non-linear numerical modeling of masonry groin vaults of major historical importance: St John Hospital case study in Jerusalem. (1st September 2019) - Milani, Gabriele; Valente, Marco; Fagone, Mario; Rotunno, Tommaso; Alessandri, Claudio
Highlights: Advanced numerical analysis of an historical masonry groin vault of major importance. Detailed homogeneous 3D-FE approach with concrete damage plasticity CDP material. Rigid body and spring RBS model with heterogeneous lateral arches. Kinematic limit analysis KLA with few NURBS elements and progressive mesh adaptation. Comparison with 1:5 in scale model experimentally tested and FRP reinforcement. Abstract: This study presents three advanced non-linear modeling strategies for the evaluation of the non-linear behavior under horizontal loads of a historical groin vault of major importance, located in Jerusalem. The vault exhibits the typical features of the Crusaders architecture, with the masonry of the bearing structure, such as the piers and the main arches, made of big stocky stones with a high quality surface finish, and the vaults made of smaller irregular cobblestones. The first model is based on a FE Concrete Damage Plasticity (FE-CDP) macroscopic approach implemented in Abaqus, where masonry is assumed elasto-plastic with damage in both tension and compression and scarcely resistant to tensile stresses. The second model is a non-commercial Rigid Body and Spring (RBS) model, where the structure is discretized into rigid elements and elasto-plastic with softening interfaces. The arches are modeled with a heterogeneous approach, whereas the vault itself through an isotropic material with quasi zero tensile strength and softening behavior. The last model is based on Kinematic Limit Analysis with adaptive mesh and consists of few rigid infinitely resistant NURBS elements (NURBS-KLA). For validation purposes, at the University of Florence a 1:5 scale model of the groin vault was tested under horizontal loads up to collapse, also in presence of FRP reinforcement glued at the extrados after the activation of the collapse mechanism in the unreinforced case. Excellent agreement with experimental results is obtained for all the models, both in terms of load carrying capacity prediction and active failure mechanism, also in presence of FRP reinforcement. The reliability of the procedures presented is therefore demonstrated.